Do Electronic Information Resources Improve Student Academic Performance? Case at the Student of Management Study Program in Yogyakarta Indonesia - Heru Kristanto, R. Heru Kristanto HC; Wahyuni, Purbudi (Technium Social Sciences Journal, 2021)
The use of information technology is an integral part of the learning process in the University. The research aimed to find out empirical evidence of the impact of electronic information resources on improving the academic performance of students in the Management Study Program. The research model used mediation regression with SEM and the PLS statistical software. Purposive sampling with 210 respondent. Electronic information resources were measured by the availability of software application infrastructure, online journals, online databases, institutional repositories, e-books, e-journals, and websites. Electronic information resources were measured by using skills electronic information resources in the learning process, making final assignments, publications. Academic performance was measured from the teaching and learning process, publications of students, improvement of achievement index, contribution to society. The results showed that the availability of software application infrastructure, online journals, online databases, institutional repositories, e-books, e-journals, and websites had an effect on academic performance. Habits or use fullness of using electronic information resources mediated the effect of electronic information resources on academic performance.